2019
DOI: 10.1021/jacs.9b00574
|View full text |Cite
|
Sign up to set email alerts
|

Element Replacement Approach by Reaction with Lewis Acidic Molten Salts to Synthesize Nanolaminated MAX Phases and MXenes

Abstract: Nanolaminated materials are important because of their exceptional properties and wide range of applications. Here, we demonstrate a general approach to synthesize a series of Zn-based MAX phases and Cl-terminated MXenes originating from the replacement reaction between the MAX phase and the late transition metal halides. The approach is a top-down route that enables the late transitional element atom (Zn in the present case) to occupy the A site in the pre-existing MAX phase structure. Using this replacement … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
763
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 1,049 publications
(837 citation statements)
references
References 49 publications
17
763
1
1
Order By: Relevance
“…Figure 3 In order to further determine the structure of Nb2CuC, STEM was performed. Figure 4 The incorporation of transition elements (Zn, Cu) into A site of MAX phase has been discussed in our previous reports where chloride salts were used [10,14]. Here, we used an alternative molten salt CuI, which has a melting point of 600°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 In order to further determine the structure of Nb2CuC, STEM was performed. Figure 4 The incorporation of transition elements (Zn, Cu) into A site of MAX phase has been discussed in our previous reports where chloride salts were used [10,14]. Here, we used an alternative molten salt CuI, which has a melting point of 600°C.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to Ti2AlN, the (103), (104), and (106) peaks are shifted towards lower angles. The (002) peak is almost vanished and the (004) peak becomes strong, indicating a change in periodic symmetry along the c axis and corresponding change in structure factor [10]. The EDS measurement (Figure 1(b)) on the resultant particles provide a semi-quantitative estimation of the atomic ratios, with of Ti:(Cu+Al) and…”
Section: Characterization and Density Functional Theory Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a nuclear magnetic resonance (NMR) spectroscopic study showed that Ti 3 C 2 T x produced by in situ formation of HF (from HCl and LiF reaction) contains considerably fewer fluorine terminations than that synthesized with HF solution directly [28]. Recently, alternative synthesis routes were able to produce fluorine-free terminations [29][30][31][32][33][34][35] and even fully chlorinated MXenes [34].…”
Section: Preparation Of Mxenementioning
confidence: 99%
“…The few nitride MXenes reported were obtained using a molten eutectic fluoride salt mixture of LiF, NaF and KF at high temperatures [37] or by ammoniation of previously obtained carbide MXenes [38]. Fluorine-free syntheses are still arguably still barely explored by the literature, with only a few methods reported such as electrochemical etching [29][30][31], hydrothermal alkali treatment [32,33,35] and reaction with Lewis acidic molten salt [34]. For a more complete overview of the different synthesis' routes toward MXenes and other ultrathin 2D transition metal carbides and nitrides to date, the reader can refer to Verger et al works [10,39].…”
Section: Preparation Of Mxenementioning
confidence: 99%